When I evaluate f(x)= -x^3 for f(a+h)

How is it suppose to look? I'm not sure what to do with the negative in front of the x

f(a+h) =-[(a+h)(a+h)(a+h)]

or

f(a+h) = [(-a-h)(-a-h)(-a-h)]

Printable View

- Jun 26th 2010, 10:54 PMsuperduper1f(x) = -x^3 evaluating for f(a+h)
When I evaluate f(x)= -x^3 for f(a+h)

How is it suppose to look? I'm not sure what to do with the negative in front of the x

f(a+h) =**-**[(a+h)(a+h)(a+h)]

or

f(a+h) = [(-a-h)(-a-h)(-a-h)] - Jun 26th 2010, 11:12 PMCaptainBlack
- Jun 27th 2010, 12:35 AMsuperduper1
I'm not sure what I'm doing wrong. The answer I get is incorrect.

f(x) = -x^3

evaluate for f(a+h)-f(a) / h

f-(x^3)= -a^3-3a^3h-3ah^2-h^3

Then when I evaluate for f(a) I get:

f(a) = -a^3

After the -a^3 subtract each other out...I factor out an h from the numerator to cancel out an h from the denominator and get:

-3a^3 - 3ah-h^2 - Jun 27th 2010, 12:45 AMCaptainBlack
- Jun 27th 2010, 05:21 AMHallsofIvy
Probably a typo. The second term should be "-3a^2h", not "-3a^3h".

Quote:

Then when I evaluate for f(a) I get:

f(a) = -a^3

After the -a^3 subtract each other out...I factor out an h from the numerator to cancel out an h from the denominator and get:

-3a^3 - 3ah-h^2